PERAN PRAKTIK PENGALAMAN LAPANGAN (PPL) DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK CALON GURU - Margaretha Ema Tukan; Maria Rasita Ina Heli (CV. Adiba Aisha Amira, 2025)
Education plays a crucial role in nurturing the potential of learners towards spiritual, personality,skills, and intellectual development. The focus on the learning process significantly influences the achievement of educational goals, with teachers playing a pivotal role in this process.Pedagogical competence becomes a critical skill for teachers but is also vital for students as prospective educators when undertaking Field Experience Practice (FEP). This research explores students' understanding of FEP and their pedagogical abilities. A qualitative phenomenological research method was employed. Three students from the Smaratungga Buddhist College of Religious Sciences, who participated in FEP for 2 months at both junior and senior high school levels, were the subjects of this research. Data were collected through interview, observation, and documentation techniques.The results indicate that students have a good understanding of FEP and pedagogical competence. They acknowledge the importance of pedagogical skills within the context of FEP. However, there is room for improvement in practically applying these competencies during teaching and learning activities.In conclusion, prospective teacher students demonstrate a good understanding of FEP and pedagogical competence. Nevertheless, there is potential for improvement in the practical application of pedagogical competencies during teaching activities. This study emphasizes the significance of understanding FEP and pedagogical competencies for the future of teacher education.